Genes and proteins associated with ribeye area and meat tenderness in a commercial Nellore cattle population - Frezarim, Gabriela B. [UNESP]; Fonseca, Larissa F S [UNESP]; Salatta, Bruna M. [UNESP]; Silva, Danielly B S [UNESP]; Bresolin, Tiago [UNESP]; Oliveira Seno, Leonardo de; Barufatti, Alexéia; Ferro, Jesus Aparecido [UNESP]; Albuquerque, Lucia Galvão [UNESP] (Canadian Science Publishing, 2022)
Despite several studies on genetic markers and differentially expressed genes related to ribeye area (REA) and tenderness traits in beef cattle, there is divergence in the results regarding the genes associated with these traits. Thirteen genes associated with or exhibiting biological functions that might influence such phenotypes were included in this study. A total of five genes for REA (IGF-1, IGF-2, MSTN, NEDD4, and UBE4A) and eight genes for meat tenderness (CAPN1, CAPN2, CAST, HSPB1, DNAJA1, FABP4, SCD, and PRKAG3) were selected from previous studies on beef cattle. Genes and their respective proteins expression were validated in a commercial population of Nellore cattle using quantitative real-time PCR (RT-qPCR) and advanced mass spectrometry (LC/MS-MS) techniques, respectively. The MSTN gene was upregulated in animals with low REA. The CAPN1, CAPN2, CAST, HSPB1, and DNAJA1 genes were upregulated in animals with tough meat. The proteins translated by these genes were not differentially expressed. Our results confirm the potential of some of the studied genes as biomarkers for carcass and meat quality traits in Nellore cattle.
Keywords: beef cattle; biological processes; bovins de boucherie; expression génique; gene expression; meat quality; processus biologiques; qualité de la viande; zebu; zébu